Centurion Perfect Squares: A Class of Perfect Squares - P. Navaneethan; R. Arumuganathan (International Journal of Mathematics And its Applications, 2025)
This paper introduces a new class of perfect squares known as Centurion Perfect Squares (CPS). This is applicable to years which can be looked at as perfect squares with 4 digits~as well the last two digits, ignoring the Century part. Conditions for a Perfect Square to be a Centurion Perfect Square have been derived by way of characterization. Illustrations also provided.